Optimal growth economics an investigation of the contemporary issues and the prospect for sustainable growth - Islam, Sardar M. N., 1950- (Contributions to economic analysis ;, 2001)
Optimal Growth Economics is concerned with the investigation of the contemporary issues in general economics, and growth economics and in the formulation of optimal growth programs, especially the issue of the sustainability of growth. This book proposes the development of optimal growth economics as a distinct, coherent and practical discipline useful for social choice by using the techniques of mathematical modelling and computing to address a wide range of emerging and enduring issues in economics. A considerable number of optimal economic growth models have been developed in the book to address the crucial issues of different branches in economics, including growth and development economics, economic planning, welfare economics, environmental economics, human capital development, political economy, natural resources and the economics of uncertainty.